2013
DOI: 10.1098/rspb.2012.2368
|View full text |Cite
|
Sign up to set email alerts
|

Trans-generational effects of prenatal stress in quail

Abstract: The prenatal environment is a source of phenotypic variability influencing the animal's characteristics. Prenatal stress affects not only the development of offspring, but also that of the following generation. Such effects have been best documented in mammals but can also be observed in birds, suggesting common processes across phylogenetic orders. We found previously that Japanese quail females stressed during laying produced offspring with higher fearfulness, probably related to modulation of testosterone l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Examples of transgenerational effects of early-life conditions are quite abundant, especially in the biomedical, epidemiological and toxicological literature on humans and rodents (reviewed in refs 1 and 17). Studies showing transgenerational inheritance of phenotypic traits programmed by early-life conditions are more limited6061 (but see rodents5360626364; birds506566). However, most of these studies have shown transgenerational transmission at a single phenotypic level.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of transgenerational effects of early-life conditions are quite abundant, especially in the biomedical, epidemiological and toxicological literature on humans and rodents (reviewed in refs 1 and 17). Studies showing transgenerational inheritance of phenotypic traits programmed by early-life conditions are more limited6061 (but see rodents5360626364; birds506566). However, most of these studies have shown transgenerational transmission at a single phenotypic level.…”
Section: Discussionmentioning
confidence: 99%
“…Precocial birds, particularly gallinaceans, are choice models for investigating genetic (Agnvall et al, ), epigenetic (Goerlich et al, ), prenatal (Guibert et al, ), and postnatal (Shimmura et al, ; Pittet et al, ) components of behavioral ontogeny. The increasing interest for these species' behavioral development requires information concerning the ontogeny of sex differences.…”
mentioning
confidence: 99%
“…More recent studies showed that male rats prenatally exposed to stress showed reduced testosterone levels, delayed latency to the first mount or first intromission, and also decreased number of ejaculations [17]. Similarly, sexual behavior of prenatally stressed male birds is reported to be impaired [18]. These effects will be more difficult to identify in humans due to much lower fertility and, if they hold, they can be counterbalanced by a desire for a large family size, less adequate use of contraception or infertility treatment.…”
Section: Discussionmentioning
confidence: 99%